Materialisierte Entfremdung. ,Schöpferisches Verfahren‘ in Marlen Haushofers Die Wand (Altre Modernità, 2021)
The central subject of Marlen Haushofer's famous novel The Wall is thereflection of alienation as “relationship of relationshiplessness” (Rahel Jaeggi). Itreflects on this by resorting to a metaphor for alienation that has become topical: theglass wall. The novel's innovative literary effort is that it takes this metaphor literally inthe form of a wall that suddenly appears and extends endlessly into the world. Thisliteralization of the metaphor, however, does not result in overcoming alienation inthe sense of liberating the nameless main character. Rather, it is part of a genuinelycreative procedure – a procedure that Deleuze and Guattari, following Franz Kafka, call“way out”. And a procedure for which the protagonist must pay the price of aninescapable ambivalence.